GAMBARAN PENGETAHUAN DAN SIKAP IBU HAMIL PRIMIGRAVIDA TERHADAP PERUBAHAN FISIOLOGIS TUBUH YANG TERJADI SELAMA MASA KEHAMILAN DI WILAYAH KERJA PUSKESMAS REJOSARI PEKANBARU - Intan, Nur; Restuastuti, Tuti; Pangaribuan, Eddy R (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTAlmost all of the primigravidae’s mothers (the first time for mother pregnancy) felt uncomfortable because of fisiological and anatomical changing which occured for their body, like hormonal changing, shaped of the body, even psicological emosional condition. Aim of this study is to know knowledge grade and attitude of primigravidae’s mothers for fisiological changing which occured during pregnancy. This study was used descriptive quantitative design with cross sectional approachment. This study has been done in Puskesmas Rejosari Region in Pekanbaru. Samples for this study was 50 persons with total sampling interpretation technique. Result for this study showed the knowledge grade of primigravidae’s mothers for fisiological changing with good categorized was 27 (54%) respondents, mid categorized was 18 (36%) respondents and bad categorized was 5 (10%) respondents. Meanwhile for results for attitude of primigravidae’s mothers for fisiological changing had positive categorized was 39 (78%) respondents, neutral was 11 (22%) respondents and negative was 0 (0%) respondents. From this study showed that the knowledge grade of primigravidae’s mothers about fisiological changing in Puskesmas Rejosari region at Pekanbaru was good that was 27 (54%) and primigravidae’s mothers about fisiological changing was positive that was 39 (78%).Key Words : knowledge, attitude, primigravidae, fisiological changing